Correlation of phospholipase and proteinase production of Candida with in vivo pathogenicity in Galleria mellonella - Rossoni, Rodnei Dennis [UNESP]; Barbosa, Júnia Oliveira [UNESP]; Vilela, Simone Furgeri Godinho [UNESP]; Santos, Jéssica Diane Dos [UNESP]; Jorge, Antonio Olavo Cardoso [UNESP]; Junqueira, Juliana Campos [UNESP] (Faculdade de Odontologia de Piracicaba - UNICAMP, 2013)
An essential factor to the virulence of the genus Candida is the ability to produce enzymes and this may be crucial in the establishment of fungal infections. AIM:This study investigated in vitro enzymatic activities of Candida species and their virulence in an in vivo Galleria mellonella experimental model. METHODS: Twenty-four clinical strains of Candida spp. isolated from the human oral cavity were evaluated, including the following species: C. albicans, C. dubliniensis, C. glabrata, C. tropicalis, C. krusei, C. parapsilosis, C. norvegensis, C. lusitaniae and C. guilliermondii. All Candida strains were tested in vitro for production of proteinase and phospholipase. The Candida strains were also injected into Galleria mellonella larvae to induce experimental candidiasis, and after 24 hours, the survival rate was assessed. RESULTS: Phospholipase and proteinase activity were observed in 100% of the C. albicans strains. In the non-albicans species, proteinase and phospholipase activity were observed in 25 and 43% of the studied strains, respectively. The most pathogenic Candida species in G. mellonella were C. albicans, C. dubliniensis and C. lusitaniae, whereas C. glabrata was the least virulent species. Furthermore, a positive significant correlation was found between both enzymatic activities with virulence in G. mellonella. CONCLUSIONS: The virulence of Candida strains in G. mellonella is related to the quantity of proteinases and phospholipases production of each strain.
Keywords: Candida; virulence factors; invertebrates